Variation of Organic Pore Structure With Maceral Types in the Longmaxi Shale, Sichuan Basin - Pang, Qian; Hu, Guang; Hu, Chaowei; Zhang, Cong (Frontiers in Earth Science, 2021)
Organic matter (OM), composed of various macerals, has a strong influence on the enrichment of shale gas. Nevertheless, the connection between OM-hosted pore structure and maceral type is not yet fully understood because of the difficulty to identify the maceral types by traditional scanning electron microscope (SEM). Using a combination of the reflected light microscopy, focused ion beam SEM (FIB-SEM), and Raman spectrum, three maceral types, including alginite, graptolite, and solid bitumen, are identified in the Longmaxi Shale of the Sichuan Basin. The alginate is characterized by the linear arrangement of OM-hosted pores due to the inherited biological structure of benthic algae. Pores in the structureless solid bitumen are randomly distributed with the highest abundance. The graptolite containing pore rarely is unfavorable for the pore generation but can be a good proxy for thermal maturity. Variation in thermal maturity levels accounts for the change of total pore volume in a given marcel type in the Longmaxi Shale obtained from different shale gas fields.